Life cycle of the centrally planned economy: Why soviet growth rates peaked in the 1950s - Vladimir Popov (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
The highest rates of growth of labor productivity in the Soviet Union were observed not in the 1930s (3% annually), but in the 1950s (6%). The TFP growth rates by decades increased from 0.6% annually in the 1930s to 2.8% in the 1950s and then fell monotonously becoming negative in the 1980s. The decade of 1950s was thus the golden period of Soviet economic growth. The patterns of Soviet growth of the 1950s in terms of growth accounting were very similar to the Japanese growth of the 1950s-70s and to Korean and Taiwanese growth in the 1960-80s - fast increases in labor productivity counterweighted the decline in capital productivity, so that the TFP increased markedly. However, high Soviet economic growth lasted only for a decade, whereas in East Asia it continued for three to four decades, propelling Japan, South Korea and Taiwan into the ranks of developed countries. This paper offers an explanation for the inverted U-shaped trajectory of labor productivity and TFP in centrally planned economies (CPEs). It is argued that CPEs under-invested into the replacement of the retiring elements of the fixed capital stock and over-invested into the expansion of production capacities. The task of renovating physical capital contradicted the short-run goal of fulfilling plan targets, and therefore Soviet planners preferred to invest in new capacities instead of upgrading the old ones. Hence, after the massive investment of the 1930s in the USSR, the highest productivity was achieved after the period equal to the average service life of fixed capital stock (about 20 years) - before there emerged a need for the massive investment into replacing retirement. Afterwards, the capital stock started to age rapidly reducing sharply capital productivity and lowering labor productivity and TFP growth rates.
Keywords: 330; Arbeitsproduktivität; Wirtschaftswachstum; Planwirtschaft; Sowjetunion